APLIKASI PRESENSI JEMAAT BERBASIS DIGITAL PADA GEREJA SION OEPURA KUPANG - Dethan, Minarni Anaci; OEmatan, Herly Maltelda; Windya, Yemima Eka Christi (Jurnal Abdimas Musi Charitas, 2024)
As a non-profit religious institution, a church relies heavily on accurate and timely information to support its decision-making processes, including the recording of congregation attendance at each service. GMIT Sion Oepura, however, has traditionally depended on manual methods using a hand tally counter, which often leads to data inaccuracies and delays in disseminating information. Through this Community Service Program (Kegiatan Pengabdian kepada Masyarakat – PKM), a digital accounting information system utilizing Android-based smartphones was implemented to record congregation attendance in real time. This initiative improved data accuracy, streamlined administrative workflows, and facilitated more efficient dissemination of information to the congregation, thereby significantly enhancing the church’s overall transparency and accountability. Moreover, the positive feedback from both congregants and church administrators suggests that this innovation has substantial potential to be adopted in other church environments as a more effective, technology-driven organizational management model.